Screening for the presence of the metacercariae of Paragonimus westermani and other organisms in the gills of the freshwater crabs at Mag-Aso River, Jaro, Leyte - Nacorda, Rian Glee M.; Cordero, Paciente A.
A negative findings on the presence of the metacercaria was obtained indicating a probable absence of the fluke in the river. Other organisms, on the other hand were present in the gills of the crabs.